Modulation of growth, microcystin production, and algal-bacterial interactions of the bloom-forming algae Microcystis aeruginosa by a novel bacterium recovered from its phycosphere - Xiao, Yao; Du, Mijia; Deng, Yang; Deng, Qinglin; Wang, Xin; Yang, Yiwen; Zhang, Binghuo; Zhang, Yu-Qin (Frontiers in Microbiology, 2024)
Harmful algal blooms (HABs) in natural waters are of escalating global concern due to their detrimental impact on environmental health. Emerging evidence indicates that algae-bacteria symbionts can affect HAB features, though much about this interplay remains largely unexplored. The current study isolated a new species of Mucilaginibacter (type strain JXJ CY 39 T ) from culture biomass of the bloom-causing Microcystis aeruginosa FACHB-905 (Maf) from Lake Dianchi, China. Strain JXJ CY 39 T was an aerobic, Gram-stain-negative rod bacterium that grew at 5-38°C, pH 4.0-11.0, and 0-3.0% NaCl. Taxonomic evaluation proposed a new species, with Mucilaginibacter lacusdianchii sp. nov., as the species epithet. Experimental results revealed that strain JXJ CY 39 T spurred the growth of Maf by supplying soluble phosphorus and nitrogen during cultivation, despite the unavailability of soluble phosphorus and nitrogen. Additionally, by producing the plant hormone indole-3acetate, strain JXJ CY 39 T possibly impacted Maf's functionality. Results from coculture experiments with other strains from Maf biomass showed possible effects of strain JXJ CY 39 T on the relationship between Maf and other cohabiting bacteria, as well as microcystin toxin production characteristics. Although Maf could foster the growth of strain JXJ CY 39 T by supplying organic carbon, the strain's growth could be regulated via specific chemical compounds based on antibiotic assays. Community composition analysis disclosed that this Mucilaginibacter strain positively affected Maf's growth and modified densities and types of bacteria linked to Maf. Overall, these results suggest that the interactions between important HAB-causing organisms and their attached bacteria are complex, dynamic, and may influence the growth characteristics of algae.